2008
DOI: 10.1007/s11237-008-9007-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of specific interactions on the sorption characteristics of porous complexes of 3d metals with derivatives of 4,4′-diazophenyl

Abstract: Coordination compounds of 3d metals with ligands -azoderivatives of benzidine and 2-hydroxybenzoic acids or 8-hydroxyquinoline -are shown to be characterized by a porous structure capable of absorbing substances of various types. The type of adsorbate is considerably influenced by the specific absorption volume of the complex.Porous coordination compounds (PCC) are widely used as catalysts for a variety of reactions, working solids for sensor structures, sorbents for separating different substances and for sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The nonclassical alcohol sorption and desorption isotherms29 of 1 and 2 imply that interaction of complexes 1 and 2 with these alcohols results in structural rearrangements, most likely associated with separation of the chains. The maximum sorption capacity is governed not by the total volume of voids as estimated from the X‐ray structure determinations, but by the interplay between the energy of interaction of substrate with structural units of the coordination compound and the energy of interaction of the structural elements within the crystal lattice (in other words, between the force that separates the Cu 5 units and the force that holds them together) 30. Since the N 2 sorption experiments indicated that the desolvated samples of 1 and 2 contained no pores (note that N 2 suffusion without sorption at 77 K is not possible), different host‐guest interaction energies and different crystal lattice energies may be the reason for the differences in the sorption capacities found for compounds 1 and 2 in methanol and ethanol sorption experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The nonclassical alcohol sorption and desorption isotherms29 of 1 and 2 imply that interaction of complexes 1 and 2 with these alcohols results in structural rearrangements, most likely associated with separation of the chains. The maximum sorption capacity is governed not by the total volume of voids as estimated from the X‐ray structure determinations, but by the interplay between the energy of interaction of substrate with structural units of the coordination compound and the energy of interaction of the structural elements within the crystal lattice (in other words, between the force that separates the Cu 5 units and the force that holds them together) 30. Since the N 2 sorption experiments indicated that the desolvated samples of 1 and 2 contained no pores (note that N 2 suffusion without sorption at 77 K is not possible), different host‐guest interaction energies and different crystal lattice energies may be the reason for the differences in the sorption capacities found for compounds 1 and 2 in methanol and ethanol sorption experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, from the shape of the absorption isotherms, it may be concluded that interaction of complex 1 with ethanol results in structural rearrangement, probably associated with separation of Cu 15 Cr 2 units. In such case maximal absorption capacity is governed by the interplay between the energy of interaction of substrate with structural units of the coordination compound and the energy of the crystal lattice 21. Nonetheless, the quantity of absorbed alcohol is comparable with the sorption capacity of porous MOFs vs. similar substrates 22…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of specific interactions and of limitations in respect of the accessibility of the pores due to the size of the sorbate molecules analysis of the sorption isotherms of various substances (including nitrogen at 77 K, hydrocarbons and methanol at 298 K) gives very similar values [40]. The possibility of specific interactions is determined by the chemical nature of the sorbate and the surface and by the ability to form chemical (most often hydrogen) bonds between the molecules of the sorbate and the sorbent [41,42]. It is also worth mentioning that in the case where DG for the specific interactions is comparable with DG for the structural or conformational rearrangement of the MOF the adsorption of the substrate can be accompanied by an increase in the volume of the pores (the effect of "breathing" or swelling of the sample).…”
Section: General Aspects Of the Determination Of The Sorption Charactmentioning
confidence: 99%